The afterlives of the Terror : facing the legacies of mass violence in post-revolutionary France - Steinberg, Ronen, 1970- (Cornell University Press, 2019)
"The book is about how those who experienced the violence of the French Revolution struggled to come to terms with it in the following decades"--